Use of Interplay between A‐Site Non‐Stoichiometry and Hydroxide Doping to Deliver Novel Proton‐Conducting Perovskite Oxides. Issue 37 (26th August 2021) - Lee, Jin Goo; Naden, Aaron B.; Savaniu, Cristian D.; Connor, Paul A.; Payne, Julia L.; M. Skelton, Jonathan; Gibbs, Alexandra S.; Hui, Jianing; C. Parker, Stephen; Irvine, John T. S.
Abstract: The magnitude of ionic conductivity is known to depend upon both mobility and number of available carriers. For proton conductors, hydration is a key factor in determining the charge–carrier concentration in ABO3 perovskite oxides. Despite the high reported proton mobility of calcium titanate (CaTiO3 ), this titanate perovskite has thus far been regarded as a poor proton conductor due to the low hydration capability. Here, the enhanced proton conductivity of the defective calcium titanate Ca0.92 TiO2.84 (OH)0.16 prepared by replacing lattice oxygens with hydroxyl groups via a solvothermal route is shown. Conductivity measurements in a humidified Ar atmosphere reveal that, remarkably, this material exhibits one order of magnitude higher bulk conductivity (10 −4 Scm −1 at 200 °C) than hydrated stoichiometric CaTiO3 prepared by traditional solid‐state synthesis due to the higher concentration of protonic defects and variation in the crystal structure. The replacement of Ca 2+ by Ni 2+ in the Ca1− x Ti1 O3−2 x (OH)2 x, which mostly exsolve metallic Ni nanoparticles along orthorhombic (100) planes upon reduction, is also demonstrated. These results suggest a new strategy by tailoring the defect chemistry via hydration or cation doping followed by exsolution for targeted energy applications. Abstract : A‐site deficient hydrated perovskite oxides developed by direct replacement of lattice oxygen with hydroxide, show one order of magnitude higher proton conductivity with ten times higher hydration. Furthermore, they allow Ni 2+ to be exsolved on the truncated edges from the A‐sites of the perovskite.